2011
DOI: 10.3892/ijo.2010.852
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus blazei Murill enhances doxorubicin-induced apoptosis in human hepatocellular carcinoma cells by NFκB-mediated increase of intracellular doxorubicin accumulation

Abstract: Abstract. It has been demonstrated that the Agaricus blazei Murill (ABM) mushroom, which primarily consists of polysaccharides, possesses anti-tumor activities. However, the mechanisms by which ABM inhibits human hepatocellular carcinoma growth remain unknown. Our study demonstrates that ABM acts as an enhancer to sensitize doxorubicin (Dox)-mediated apoptotic signaling, and this sensitization can be achieved by enhancing intracellular Dox accumulation via the inhibition of NFκB activity. These findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…NF-κB regulates cell survival and its activation contributes to drug resistance via inhibiting the pro-apoptotic effects of chemotherapy. The studies demonstrated that Agaricus blazei and Hericium erinaceus could sensitize doxorubicin-mediated apoptosis through inhibiting NF-κB activation [ 146 , 147 ]. It was reported that the PI3K/AKT pathway contributed to drug resistance of cancer cells, and inactivation of the pathway by Pleurotus pulmonarius significantly enhanced the sensitivity of HCC cells to cisplatin [ 134 ].…”
Section: Effects Of Combination Of Dietary Natural Products With Amentioning
confidence: 99%
“…NF-κB regulates cell survival and its activation contributes to drug resistance via inhibiting the pro-apoptotic effects of chemotherapy. The studies demonstrated that Agaricus blazei and Hericium erinaceus could sensitize doxorubicin-mediated apoptosis through inhibiting NF-κB activation [ 146 , 147 ]. It was reported that the PI3K/AKT pathway contributed to drug resistance of cancer cells, and inactivation of the pathway by Pleurotus pulmonarius significantly enhanced the sensitivity of HCC cells to cisplatin [ 134 ].…”
Section: Effects Of Combination Of Dietary Natural Products With Amentioning
confidence: 99%
“…It is one of the most important edible and culinary medicinal species. [7778] It is cultivated commercially for the health food market and is shown to possess a range of medicinal properties against diseases like cancer[7980] and chronic hepatitis. [81] Preclinical studies have shown it to possess anti-inflammatory effects against a range of ulcerogens.…”
Section: Dietary Agents With Anti-ibd Effectsmentioning
confidence: 99%
“…Moreover, DOX causes early activation of p53 in tumor cells. Upon activation of the p53 pathway, the expression of the apoptotic regulatory protein, B-cell lymphoma 2 (Bcl-2) is decreased, whereas the downstream caspases, caspase-9, and caspase-3 are activated, leading to apoptosis [ 36 ]. However, the clinical use of DOX is limited by its severe side effects and the associated developed drug resistance, thus, single-agent chemotherapy is no longer appropriate for treating human tumors.…”
Section: Introductionmentioning
confidence: 99%